Ao haru ride. Volume 6 - Sakisaka, Io (Shojo beat manga., 2019)
"Futaba Yoshioka has encountered her first love again in high school, but he seems different from the boy she once knew. Futaba feels that the distance between her and Kou has grown since he and Yui have started keeping in touch. Then something unexpected happens between Futaba and Kou at the school festival."--Page [4] of cover.